STRATEGI PENYIAR DALAM MENJAGA EKSISTENSI RADIO TASYAFM 104,2 MHZ DI KUBANG KABUPATEN LIMA PULUH KOTA - Lailatul Munawarah; Tomi Hendra (KOLONI, 2023)
Radio announcer is the main key in radio broadcasting, therefore the progam that has been compiled on the radio will not be successful without the announcer as the person in charge of broadcasting it. The purpose of this study is determine how the strategy broadcasters and the application of these strategies to create communication effective and maintain the existence of the radio. The theory used  in this study is the theory of broadcasting strategy by Susan Tyler Eastman. This research uses qualitative methods be descriptive. Sources of data in this study came from informants reseach and documentation. Data collection is done by observation, interviews, documentation, and library studies. Based on research conducted on radio Tasya FM, found of the strategy implemented by radio bradcasters include strategy as the concept of conformity strategy, habit formation strategy, strategy listener flow control, storage strategies progam sources, and mass atraction strategy that fits with the broadcasting strategy by Susan Tyler Easman. Keywords: Broadcasting strategy, Tasya FM radio, Existence